PENGARUH PAJAK, BONUS PLAN, TUNNELING INCENTIVE, DAN UKURAN PERUSAHAAN TERHADAP TRANSFER PRICING - MARISA, RATNA (Jurnal Akuntansi AKUNESA, 2017)
Globalization and the existence of ASEAN Economic Community decrease the boundaries between countries, the freedom of transaction among affiliated company is presumed will increase transfer pricing. Majority shareholder usually will do transfer pricing to transfer their asset for personal interest. Transfer pricing makes the country suffered many losses especially in term of taxation. This study uses quantitative approach and multiple regression method. Using sample of companies listed on the Indonesian Stock Exchange from 2012 untill 2014, with dependent variable is transfer pricing, measured by Related Party Transaction, and the independent variable are tax, bonus plan, tunneling incentive, and the size of the company, this study finds that tunneling incentive and the size of the company positively impact on accounting conservatism. Whereas, tax and bonus plan have no impact on transfer pricing. Keywords: bonus plan, firm size, tax, transfer pricing, tunneling incentive.